STUDY THE OPERATIONAL BEHAVIOR OF PV GENERATOR WITH ENVIRONMENTAL CONDITION - Brahmaiah, V.Siva; Tyagi, Sachin; Adhikari, Manav (International Journal of Engineering Technologies and Management Research, 2016)
The combination of series and parallel connected PV modules made Photovoltaic (PV) generator. In this PV generator the level of current is increased by parallel connection and voltage level is increased by series connection. In grid connected applications high level of voltage is require for synchronizing the system with connected PV generator. PV generator operation gives harmful effects due to partial shading. The series connection is more prone to these effects than a parallel connection. In this thesis simulation model of PV generator is made by using MATLAB Simulink software and different configuration analysis can be taken out.